Organizing knowledge - Brown, John Seely (California management review)
Countering claims that cyberspace will bring the end of organizations in general and of the firm in particular, this article points to the role organizations play in fostering the production and synergistic development of knowledge. Formal organizations help turn the partial, situated insights of individuals and communities into robust, organizational knowledge. To organize knowledge in this way requires acknowledging the boundaries inevitably erected within organizations through the division of labor and the division of knowledge. Infrastructure for organizing knowledge must overcome these boundaries. Assuming that knowledge is a frictionless commodity possessed by individuals makes communications technologies and social organization curious antagonists. This article argues instead for compatible organizational and technological architectures that respond to and enhance the social production of knowledge.